Screen Time and Autism: Current Situation and Risk Factors for Screen Time Among Pre-school Children With ASD - Dong, Han-Yu; Feng, Jun-Yan; Wang, Bing; Shan, Ling; Jia, Fei-Yong (Frontiers in Psychiatry, 2021)
Objective：To investigate the current status of screen time in children with ASD, its correlation with autistic symptoms and developmental quotient(DQ), and the factors affecting screen time. Method：One hundred ninety-three Chinese children with ASD were recruited. We collected the demographic and screen time data using a questionnaire. The ASD core symptoms and developmental quotient (DQ) were measured by the Autism Behavior Checklist (ABC), Childhood Autism Rating Scale (CARS), Autism Diagnostic Observation Schedule-Second Edition (ADOS-2), Griffiths Development Scales-Chinese Language Edition (GDS-C), and Chinese Children’s Parent-Child Relationship Questionnaire (CPCIS). Then, we analyzed the correlations between the screen time of children with ASD and the ABC, CARS, ADOS, GDS-C DQs, and CPCIS scores. Linear regression was used to analyze the risk factors that affect screen time. Results: The children’s average daily screen time was 2.64±2.24 hours. 48% children were exposed to 2 or more types of electronic devices. Their favorite activity of screen time was watching cartoons. Only 34% children spent screen time accompanied by parents and with communication. 50.26% children had no screen time before sleeping. The screen time of children with ASD had a negative correlation with the GDS-C CQ (r=-0.234, P=0.001) and the CPCIS score (r=-0.180, P=0.012) and a positive correlation with the CARS score (r=0.192, P=0.009). A low father’s education level(P=0.010), less restriction of the child’s screen time by the guardian (P=0.001), greater caregiver screen time (P＜0.001), the use of the screen as a tool for child rearing (P=0.001), and the child’s ownership of independent electronic equipment(P=0.027) are risk factors for long screen time in children with ASD. Conclusion: The screen time of children with ASD in China is higher than the recommended standard, and the current situation is serious. The screen time of ASD children is related to their autism symptoms, DQ and parent-child interaction. Low paternal education levels, less restriction of children’s screen time by guardians, greater guardian screen time, the use of screens in child rearing, and children’s ownership of independent electronic equipment can lead to an increase in children’s screen time. These findings may have implications for family intervention strategies.